2017
DOI: 10.1107/s1600577517000625
|View full text |Cite
|
Sign up to set email alerts
|

A novel molten-salt electrochemical cell for investigating the reduction of uranium dioxide to uranium metal by lithium using in situ synchrotron radiation

Abstract: Energy-dispersive X-ray diffraction was used to follow the reduction of UO2 to U in LiCl–KCl eutectic. A novel electrochemical cell was designed and constructed in order to follow molten-salt electrochemical investigations in situ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 23 publications
1
0
0
Order By: Relevance
“…The electrochemical reduction pathway of UO 2 in LiCl based melts has been studied extensively using transient electrochemical techniques and by X-ray diffraction technique. 33,38,[41][42][43] Most of the studies have reported direct fourelectron reduction of UO 2 to U metal without any intermediates as observed in this study. Biju Joseph et al recorded a CV of the tip of a UO 2 pellet in LiCl melt at 650 °C and reported three reduction peaks prior to lithium deposition.…”
Section: Reactionsupporting
confidence: 62%
“…The electrochemical reduction pathway of UO 2 in LiCl based melts has been studied extensively using transient electrochemical techniques and by X-ray diffraction technique. 33,38,[41][42][43] Most of the studies have reported direct fourelectron reduction of UO 2 to U metal without any intermediates as observed in this study. Biju Joseph et al recorded a CV of the tip of a UO 2 pellet in LiCl melt at 650 °C and reported three reduction peaks prior to lithium deposition.…”
Section: Reactionsupporting
confidence: 62%